2021
DOI: 10.1186/s12967-020-02681-6
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-migraine agents from an immunological point of view

Abstract: The new wave of anti-migraine agents is nothing less than a milestone in our battle to manage this devastating disease. However, concerns have recently increased regarding the safety of these drugs. CGRP, while known as a potent vasodilator, is also a key neural and immune modulator. The roles of CGRP in immune determination, have been studied in depth, with particular focus on its functional significance with respect to common immune challenges i.e., bacterial, viral, fungal and parasitic infections. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 85 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…It is previously reported that re-activation of herpes viruses, and the subsequent inflammatory response is a significant factor in DRESS [ 22 ]. In this context, CGRP has a role in the immune response to viral infection, preventing viral replication and cross-reactivity [ 10 ], and in vitro, CGRP gene expression was reduced by intra-nerve varicella zoster virus [ 23 ]. While speculative, it may be that inhibition of CGRP in this case had a role in re-activation of a herpes virus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is previously reported that re-activation of herpes viruses, and the subsequent inflammatory response is a significant factor in DRESS [ 22 ]. In this context, CGRP has a role in the immune response to viral infection, preventing viral replication and cross-reactivity [ 10 ], and in vitro, CGRP gene expression was reduced by intra-nerve varicella zoster virus [ 23 ]. While speculative, it may be that inhibition of CGRP in this case had a role in re-activation of a herpes virus.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP and CGRP receptors are expressed widely throughout the body, and as such there are several theoretical off-target effects of long-term inhibition, and these have been summarised in several recent review articles [ 6 , 9 ]. The most significant possible consequences include inhibition of angiogenesis, inhibition of vasodilation, the possibility of osteoporosis, disruption of gastrointestinal mucosal integrity and constipation [ 6 , 10 , 11 ]. To date, there have been case reports of probable migraine-related stroke, polyarthralgia, and reversible cerebral vasoconstriction syndrome possibly related to CGRP mAb use [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaps in the knowledge of migraine pathogenesis make challenging its prevention and treatment, but some migraine drugs targeting the CGRP signaling pathway, including monoclonal antibodies against the receptor or ligand and small molecule CGRP receptor antagonists, ditans, and gepants approved by the FDA, create a hope for the future [ 18 , 62 , 68 ]. It is too early to draw a definitive conclusion on newly introduced antimigraine drugs, but a meta-analysis suggests that they may be equally effective as other migraine preventive drugs but have fewer unwanted side effects and are more comfortable to use (reviewed in [ 98 ]).…”
Section: Migrainementioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author identified an error in the author name of Mushref Bakri Assas . The incorrect author name is: Bakri M. Assas The correct author name is: Mushref Bakri Assas …”
Section: Correction To: J Transl Med (2021) 19:23 101186/s12967-020-02681-6mentioning
confidence: 99%